Extensive Epitranscriptomic Methylation of A and C Residues on Murine Leukemia Virus Transcripts Enhances Viral Gene Expression - David G. Courtney (American Society for Microbiology, 2019)
ABSTRACT While it has been known for several years that viral RNAs are subject to the addition of several distinct covalent modifications to individual nucleotides, collectively referred to as epitranscriptomic modifications, the effect of these editing events on viral gene expression has been controversial. Here, we report the purification of murine leukemia virus (MLV) genomic RNA to homogeneity and show that this viral RNA contains levels of N6-methyladenosine (m6A), 5-methylcytosine (m5C), and 2′O-methylated (Nm) ribonucleotides that are an order of magnitude higher than detected on bulk cellular mRNAs. Mapping of m6A and m5C residues on MLV transcripts identified multiple discrete editing sites and allowed the construction of MLV variants bearing silent mutations that removed a subset of these sites. Analysis of the replication potential of these mutants revealed a modest but significant attenuation in viral replication in 3T3 cells in culture. Consistent with a positive role for m6A and m5C in viral replication, we also demonstrate that overexpression of the key m6A reader protein YTHDF2 enhances MLV replication, while downregulation of the m5C writer NSUN2 inhibits MLV replication. IMPORTANCE The data presented in the present study demonstrate that MLV RNAs bear an exceptionally high level of the epitranscriptomic modifications m6A, m5C, and Nm, suggesting that these each facilitate some aspect of the viral replication cycle. Consistent with this hypothesis, we demonstrate that mutational removal of a subset of these m6A or m5C modifications from MLV transcripts inhibits MLV replication in cis, and a similar result was also observed upon manipulation of the level of expression of key cellular epitranscriptomic cofactors in trans. Together, these results argue that the addition of several different epitranscriptomic modifications to viral transcripts stimulates viral gene expression and suggest that MLV has therefore evolved to maximize the level of these modifications that are added to viral RNAs.